Private Teachers’ Experiences with Parents of Students Failing Assessments in Tacloban City - Daga, Alvin Kit (LPPI Yayasan Almahmudi bin Dahlan, 2025)
This study explores the multifaceted experiences of private teachers as they navigate interactions with parents of students who have failed assessments. Utilizing an Interpretive Phenomenological Analysis qualitative research design, the study delves into the lived experiences of private teachers in selected schools in Tacloban City. Data was collected through in-depth, semi-structured interviews with teachers possessing at least five years of experience and regular involvement in parent-teacher conferences concerning academic underperformance. The findings reveal a range of communication strategies employed by teachers, including initial delegation to advisors and meticulous preparation with documented evidence for formal meetings. Parental reactions varied from understanding to disappointment and skepticism, often influenced by prior expectations. Key factors contributing to student assessment failures were identified, encompassing family problems, personal issues, lack of socialization, peer influence, student disinterest, tardiness, and procrastination, as well as pedagogical challenges. The study emphasizes the critical role of transparent and empathetic communication, guided by the Transactional Model of Communication and Epstein’s Theory of Overlapping Spheres of Influence, in fostering collaborative partnerships between teachers and parents. Ultimately, the research underscores the necessity of a holistic and individualized approach to intervention, highlighting that students' academic struggles stem from a complex interplay of internal and external factors, and that active parental involvement is crucial for academic success.